2003
DOI: 10.1002/pd.590
|View full text |Cite
|
Sign up to set email alerts
|

Fetoplacental discrepancy involving structural abnormalities of chromosome 8 detected by prenatal diagnosis

Abstract: We describe the finding of three cell lines involving different structural abnormalities of chromosome 8 detected in a prenatal diagnosis. Chorionic villi sampling (CVS) was performed on a pregnant woman because of advanced maternal age. Semidirect cytogenetic analysis showed a mos46,XX,i(8q)/46,XX,del(8)(p11.2) karyotype, confirmed by fluorescence in situ hybridization (FISH). Amniocentesis was subsequently performed, and the karyotype obtained was 46,XX,dup(8)(p23p11.2). The pregnancy was terminated; patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Mosaicisms similar to that described here have been reported three times, twice in two children with dysmorphic features and mental retardation 18,19 and a third one in prenatal diagnosis. 17 In the latter case, a mosaic karyotype 46,XX,i(8q) /46,XX,del(8)(p11.2) was found in direct CVS, whereas in the follow-up amniocentesis only metaphases with the inv dup(8p) had been found. The authors suggested that the mosaicism del(8)(p11.2)/inv dup(8p) derives from the postzygotic breakage of a dicentric chromosome 8 formed through unequal recombination of the two pairs of olfactory receptor gene-clusters at 8p23.1.…”
Section: Inverted Duplications and Mosaicism T Pramparo Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Mosaicisms similar to that described here have been reported three times, twice in two children with dysmorphic features and mental retardation 18,19 and a third one in prenatal diagnosis. 17 In the latter case, a mosaic karyotype 46,XX,i(8q) /46,XX,del(8)(p11.2) was found in direct CVS, whereas in the follow-up amniocentesis only metaphases with the inv dup(8p) had been found. The authors suggested that the mosaicism del(8)(p11.2)/inv dup(8p) derives from the postzygotic breakage of a dicentric chromosome 8 formed through unequal recombination of the two pairs of olfactory receptor gene-clusters at 8p23.1.…”
Section: Inverted Duplications and Mosaicism T Pramparo Et Almentioning
confidence: 99%
“…Cellular selection favouring the cells with a less severe aneuploidy over those with large duplications or deletions is expected to occur as it is known to occur against trisomic cells. 25 -28 The isochromosome 8 in some cells of Soler's case 17 and the three cells of our inv dup(8p) having satellites at its tip seem to indicate that the dicentric 8 with both the centromeres still active could have been maintained for a certain duration along embryogenesis. In fact, it seems likely to assume that the isochromosome was formed through the fusion of the two chromatids in a neoformed deleted chromosome 8, which could not be healed by the telomerase any more due to the switch-off of its activity.…”
Section: Inverted Duplications and Mosaicism T Pramparo Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The dicentric chromosome, in theory, can undergo breakage during meiosis or it can be inherited as such in the zygote. A few cases of mosaicism with different derivatives of the dicentric indeed suggest that the dicentric is usually present in the zygote: both Soler et al (11) and Pramparo et al (12) found in chorionic villi samples two cell lines, one with a del(8)(p11), the other one with an inv dup del(8p). In the case analyzed by Pramparo et al, a third cell line was also present with an inv dup del(8p) ending with the satellites of a D or a G short arm, suggesting that here the inv dup del(8p) had been stabilized through telomere capture leading to a translocated inv dup del chromosome.…”
Section: History Of a Recurrent Rearrangementmentioning
confidence: 99%
“…6 7 Polymorphic markers analysis has shown that, in addition, such mosaics may originate during parental meiosis. [7][8][9][10][11][12][13][14] In this paper we describe a girl with a mosaic del(9)/ der(9)t(5;9)inv dup (9) initially diagnosed by conventional high-resolution G-banded chromosomes and characterised by array comparative genomic hybridisation (aCGH) and fluorescence in situ hybridisation (FISH). The most straightforward explanation for our findings would be an early post-zygotic error followed by independent chromosome healing of both sister chromatids by neo-telomere formation and telomere capture.…”
mentioning
confidence: 99%